Dr. Artom [Rev. Dr. Benjamin] (Tufts Archival Research Center, 2008)
2.5 x 4.25. "Rev. Dr. Benjamin Artom; Chief Rabbi of the Spanish and Portugese Jews' congregations in England; died Jan. 6 1879; aged 45 years." Clipping from newspaper article pasted on back of card. Produced by: The London Stereoscopic & Photographic Company. 110 & 108, Regent Street and 54, Cheapside. These dates are approximate.